Differential Diagnosis of Dysgraphia, Dyslexia, and OWL LD: Behavioral and Neuroimaging Evidence - Berninger, Virginia W. (Read Writ, 2015)
In Study 1, children in grades 4 to 9 (N= 88, 29 females and 59 males) with persisting reading and/or writing disabilities, despite considerable prior specialized instruction in and out of school, were given an evidence-based comprehensive assessment battery at the university while parents completed questionnaires regarding past and current history of language learning and other difficulties. Profiles (patterns) of normed measures for different levels of oral and written language used to categorize participants into diagnostic groups for dysgraphia (impaired subword handwriting) (n=26), dyslexia (impaired word spelling and reading) (n=38), or oral and written language learning disability OWL LD (impaired oral and written syntax comprehension and expression) (n=13) or control oral and written language learners (OWLs) without SLDs (n=11) were consistent withreported history. Impairments in working memory components supporting language learning were also examined. In Study 2, right handed children from Study 1 who did not wear braces (controls, n=9, dysgraphia, n= 14; dyslexia, n=17, OWL LD, n=5) completed an fMRI functional connectivity brain imaging study in which they performed a word-specific spelling judgment task, which is related to both word reading and spelling, and may be impaired in dysgraphia, dyslexia, and OWL LD for different reasons. fMRI functional connectivity from 4 seed points in brain locations involved in written word processing to other brain regions also differentiated dysgraphia, dyslexia, and OWL LD; both specific regions to which connected and overall number of functional connections differed. Thus, results provide converging neurological and behavioral evidence, for dysgraphia, dyslexia, and OWL LD being different, diagnosable specific learning disabilities (SLDs) for persisting written language problems during middle childhood and early adolescence. Translation of the research findings into practice at policy and administrative levels and at local school levels is discussed.